To find the sum \( S_{75} \) of the first 75 terms of the arithmetic sequence defined by \( a_n = 67 - 2n \), we can follow these steps:
-
Identify the first term \( a_1 \) and the 75th term \( a_{75} \):
- The first term \( a_1 \): \[ a_1 = 67 - 2(1) = 67 - 2 = 65 \]
- The 75th term \( a_{75} \): \[ a_{75} = 67 - 2(75) = 67 - 150 = -83 \]
-
Determine the number of terms \( n \):
- Here, \( n = 75 \).
-
Calculate the sum of the first \( n \) terms \( S_n \) using the formula for the sum of an arithmetic series:
- The formula is: \[ S_n = \frac{n}{2} \times (a_1 + a_n) \]
- Plugging in the values we have: \[ S_{75} = \frac{75}{2} \times (65 + (-83)) \] \[ S_{75} = \frac{75}{2} \times (65 - 83) \] \[ S_{75} = \frac{75}{2} \times (-18) \] \[ S_{75} = \frac{75 \times (-18)}{2} = \frac{-1350}{2} = -675 \]
Thus, the value of \( S_{75} \) is \(\boxed{-675}\).